Supporting the diagnosis of infantile colic by a point of care measurement of fecal calprotectin - Sommermeyer, Henning; Bernatek, Malgorzata; Pszczola, Marcin; Krauss, Hanna; Piatek, Jacek (Frontiers in Pediatrics, 2022)
Background: Infantile colic (IC) is a condition characterized by extensive crying which affects about 20% of all infants during their first months of life. Most pediatricians diagnose IC only based on their clinical experience. Aim: Investigating if a measurement of fecal calprotectin can support the diagnosis of IC. Methods: The crying behavior of newborns was assesd using the Wessel’s criteria. Fecal calprotectin levels were measured in non-colicky and colicky babies using a standard test that can be used at the time and place of patient care (point of care (PoC) measurement). Results: Colicky babies were found to have significantly elevated fecal calprotectin levels. Calprotectin levels were not influenced by gender, type of feeding, gestation age or birth weight. However, significantly elevated fecal calprotectin levels were found in caesarean section born babies. Fecal calprotectin ≥ 100 µg/g correlated with a colicky status of an infant while those < 100 µg/g indicated a non-colicky status the error margin was 11.2% and 13.2%, respectively. Combining data of fecal calprotectin with information about the type of delivery made it possible to determine the colicky status in vaginally-born infants with fecal calprotectin ≥ 100 µg/g with an accuracy of 97.8%. As elevated fecal calprotectin levels in caesarean-born infants can be caused by IC, but also by the disturbed gut microbiota commonly found in these babies, the accuracy of diagnosing the colicky status of a caesarean-born infant with calprotectin levels ≥ 100 µg/g was less accurate (accuracy rate of 76.5%). Conclusion: Data from the study suggest that measuring fecal calprotectin should be considered by pediatricians to support the diagnosis of IC. The study was registered at ClinicalTrials.gov under NCT0466324.